Analisis Kesalahan Newman Dalam Menyelesaikan Soal Cerita Ditinjau Dari Gaya Belajar Pada Siswa Kelas VIII - Baiq Sundusiah; Sri Subarinah; Nilza Humaira Salsabila (Lembaga Bale Literasi, 2025)
Story problems are problems related to real life that contain a problem to be solved. Solving story problems requires the ability to understand the content of the problem. However, many students still experience difficulties in solving story problems. The purpose of this study is to describe the types of errors and their causes among students with visual, auditory, and kinesthetic learning styles in the Pythagorean theorem material. Error analysis was conducted based on Newman's procedure. The subjects of this study were student in class VIII-1 of SMPN 3 Mataram for the 2024/2025 academic year, selected using purposive sampling. The data collection techniques used were questionnaires, story problem tests, and interviews. The data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results of the study revealed: (i) students with a visual learning style made errors in problem transformation and writing conclusions. The causes of errors made by visual learners include being careless in determining formulas, incorrectly illustrating known information, mistakenly determining formulas, not knowing the steps to solve the problem, and errors in previous stages. (ii) Students with an auditory learning style made errors in problem transformation, process skills, and writing conclusions. The causes of errors made by auditory learners include being careless in performing calculations, confusion in determining formulas, and errors in previous stages. (iii) Students with a kinesthetic learning style make errors in problem transformation, process skills, and writing conclusions. The causes of errors made by kinesthetic learners include incorrectly illustrating information, not knowing how to solve problems, answering arbitrarily, and errors in the calculation process.